Nursing students' experience during their practicum in an intensive care unit: A qualitative meta-synthesis - Liu, Yue; Wang, Lingmin; Shao, Haiyan; Han, Peng; Jiang, Jinxia; Duan, Xia (Frontiers in Public Health, 2022)
Background Clinical practicum provides nursing students with more opportunities to learn their professional knowledge and develop basic nursing skills. Intensive care unit (ICU) is often used as one of the clinical practicum departments for nursing students. Due to the characteristic fast-paced working environments, high acuity of patient care, and technical complexities of an ICU, nursing students are more susceptible to experiencing stress and lack of confidence in these settings, which hinders their professionalization and affects patient care. Objective The study aimed to summarize and evaluate the nursing students' experience in an ICU during their practicum and to provide a supportive ICU clinical practicum environment for them. One of the main objectives was to increase the ICU specialty nurse reserve and improve nursing care in the ICU. Methods The following databases were searched for related qualitative publications in Chinese and English by systematic searches across January 2022, including the nursing students' experience in ICU during their practicum: PubMed, Cochrane Library, Web of Science, and so on. The qualitative meta-synthesis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Two reviewers independently selected these studies and carefully evaluated the quality of each study. Meta-synthesis was then used to summarize the results. Results Eleven sub-themes and 3 themes were revealed in 9 studies: challenges of clinical practicum in the ICU, the expectation of support from multiple sources, and the importance and necessity of practicum in the ICU. Conclusion Performing one's practicum in ICU was considered by the nursing students in this review as a beneficial practicum despite the challenges involved. The appropriate guidance and monitoring should be given by hospital managers and college educators.